2022
DOI: 10.1371/journal.pone.0263509
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to altered auditory cues: Generalization from manual reaching to head pointing

Abstract: Localising sounds means having the ability to process auditory cues deriving from the interplay among sound waves, the head and the ears. When auditory cues change because of temporary or permanent hearing loss, sound localization becomes difficult and uncertain. The brain can adapt to altered auditory cues throughout life and multisensory training can promote the relearning of spatial hearing skills. Here, we study the training potentials of sound-oriented motor behaviour to test if a training based on manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 52 publications
(70 reference statements)
2
26
0
Order By: Relevance
“…In this respect, the interpretation of any head-movement related benefit becomes more cognitive, i.e., related to predictive behaviors that participants put in place when aiming to solve perceptual uncertainties. For asymmetrical ARHL participants, turning the head may have been an intentional strategy to exploit the headshadow effect, maximizing sound intensity at the best ear (see also Valzolgher et al, 2020bValzolgher et al, , 2022b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the interpretation of any head-movement related benefit becomes more cognitive, i.e., related to predictive behaviors that participants put in place when aiming to solve perceptual uncertainties. For asymmetrical ARHL participants, turning the head may have been an intentional strategy to exploit the headshadow effect, maximizing sound intensity at the best ear (see also Valzolgher et al, 2020bValzolgher et al, , 2022b.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although in the present study head-movements were implemented spontaneously, active head-orienting to sounds could be trained. Studies in this direction have already been conducted in normal hearing young adults with one ear plugged, to simulate a unilateral hearing loss condition (i.e., Valzolgher et al, 2020bValzolgher et al, , 2022b and in bilateral cochlear implant users (Valzolgher et al, 2022a). A relevant future direction for research would be to test training paradigms to promote effective behavioral strategies during sound localization even in ARHL.…”
Section: Discussionmentioning
confidence: 99%
“…This space is actually quite relevant for humans: the near-field portion of space is particularly relevant for social interactions, where fast motor responses are needed in case of an approaching auditory object (e.g., a mosquito), when reaching toward a sound source (e.g., our phone ringing) or when orienting toward a nearby talker. Noticeably, a recent study (Valzolgher et al 2020a , b ) has shown that the ability to interact with a sound in the reaching space improves localization performance and promotes head movements, and this interaction also benefits spatial hearing rehabilitation (Valzolgher et al 2022 ). As the participants localize sound sources manually, far-field stimulation is not feasible with our actual setup.…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, SPHERE proved sensitive for detecting and quantifying the contribution of free head motion during sound emission, with improvements to sound localization accuracy and precision. The SPHERE approach has been used recently with adult and pediatric populations, on both normal-hearing participants and cochlear implant patients (Coudert et al 2022 ; Valzolgher, et al 2020a , b , 2020a ; Valzolgher et al 2022 ). It offers a highly versatile opportunity to assess normal and pathological sound localization performance in a more ecologically valid approach (for discussion see Russell 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study of the role of bodily movements in spatial hearing has been receiving progressively more attention leading to an increasing understanding of how action influences auditory perception ( Aytekin et al, 2008 ; McLachlan et al, 2021 ; Valzolgher et al, 2022 ). In the field of auditory peripersonal studies, special attention is being paid to everyday localization responses, such as reaching for an object ( Farnè and Làdavas, 2002 ).…”
Section: Introductionmentioning
confidence: 99%